Study on Textural, Microbial and Sensory Quality of Blast Frozen Pangasius Fish Fillets Under Frozen Storage - Shrestha, Rojeena; Bokkhim, Huma (Department of Agro-industrial Technology, University of Brawijaya, 2020)
AbstractPangasius fish is one of the rapid growing fresh water species in aquaculture. This study was aimed to assess the microbial number, physical quality and sensory evaluation of the Pangasius fish fillets from Nepal. Pangasius fish were collected from Chitwan and Nawalparasi districts, fillets were prepared and blast frozen simultaneously. The microbial number decreased rapidly during storage in frozen condition while Staphlylococcus aureus and Escherichia coli (which were present initially in fillets) disappeared during storage. The sensory panellists preferred air blast frozen fillets stored for one month than stored for two months. Different parts of the fish body showed different textural properties. Hardness was increased during second month of storage while other textural properties were found satisfactory in first month of storage in frozen condition. This study showed that sensory qualities of air blast frozen Pangasius fish fillets changes with time even in frozen storage.Keywords: fillet, microbial number, Pangasius, sensory, texture AbstrakIkan Pangasius adalah salah satu spesies ikan air tawar yang dapat tumbuh cepat saat dibudidayakan. Penelitian ini bertujuan untuk menilai kualitas mikroba, kualitas fisik, dan evaluasi sensorik fillet ikan Pangasius di Nepal. Ikan Pangasius didapatkan dari daerah Chitwan dan Nawalparasi kemudian dibuat fillet dan dibekukan secara langsung. Jumlah mikroba menurun drastis saat penyimpanan dalam kondisi beku, sedangkan Staphlylococcus aureus dan Escherichia coli (yang memang ada di bahan sejak awal) tidak ada selama penyimpanan. Panelis sensoris lebih memilih fillet ikan dengan pembekuan air blast yang disimpan selama satu bulan daripada dua bulan. Bagian tubuh ikan yang berbeda menunjukkan sifat tekstur fillet yang berbeda. Tingkat kekerasan fillet ikan meningkat saat penyimpanan bulan ke dua, sementara sifat tekstur yang lain paling diminati saat penyimpanan bulan pertama dalam kondisi beku. Studi ini menunjukkan bahwa kualitas sensoris fillet ikan Pangasius dengan pembekuan air blast berubah seiring waktu bahkan dalam penyimpanan beku.Kata kunci: fillet, jumlah mikroba, Pangasius, sensori, tekstur